Randomised preference trial of medical versus surgical termination of pregnancy less than 14 weeks’ gestation (TOPS) - SC Robson; T Kelly; D Howel; M Deverill; J Hewison; MLS Lie; E Stamp; N Armstrong; CR May (Health Technology Assessment, 2009)
Objectives: To determine the acceptability, efficacy and costs of medical termination of pregnancy (MTOP) compared with surgical termination of pregnancy (STOP) at less than 14 weeks’ gestation, and to understand women’s decision-making processes and experiences when accessing the termination service. Design: A partially randomised preference trial and economic evaluation with follow-up at 2 weeks and 3 months. Setting: The Royal Victoria Infirmary, Newcastle upon Tyne, UK. Participants: Women accepted for termination of pregnancy (TOP) under the relevant Acts of Parliament with pregnancies < 14 weeks’ gestation on the day of abortion. A further group of women attending contraception and sexual health clinics participated in a discrete choice experiment (DCE). Interventions: STOP: all women ≥ 6 weeks’ and < 14 weeks’ gestation were primed with misoprostol 400 μg 2 hours before the procedure. STOP was performed under general anaesthesia using vacuum aspiration. MTOP: all women < 14 weeks’ gestation were given mifepristone 200 mg orally, returning 36–48 hours later for misoprostol. Outcome measures: Main outcome measure was acceptability of TOP method. Secondary outcome measures included strength of preference by willingness to pay (WTP); distress, using the Impact of Event Scale (IES); anxiety and depression; satisfaction with care; experience of care; frequency and extent of symptoms including self-assessment of pain; clinical effectiveness; and complications. A DCE was used to identify attributes that shape women’s preferences for abortion services. Results: The trial recruited 1877 women, 349 in the randomised arms and 1528 in the preference arms. Of those in the preference arms, 54% chose MTOP. At 2 weeks after the procedure more women having STOP would choose the same method again in the future. Acceptability of MTOP declined with increasing gestational age. The difference in acceptability between STOP and MTOP persisted at 3 months. At 2 weeks after TOP, women in the preference arms were prepared to pay more to have their preferred option. There was no difference in anxiety or depression scores in women having MTOP or STOP. However, women randomised to MTOP had higher scores on subscales of the IES at both 2 weeks and 3 months. There was no difference in IES scores between MTOP and STOP in the preference arm. Women were more likely to be satisfied overall and with technical and interpersonal aspects of care if they had STOP rather than MTOP. Experience of care scores were lower after MTOP in both randomised and preference arms. During admission women undergoing MTOP had more symptoms and reported higher mean pain scores, and after discharge reported more nausea and diarrhoea. There were no differences in time taken to return to work between groups; around 90% had returned to work and normal activity by 2 weeks. Rates of unplanned or emergency admissions were higher after MTOP than after STOP. Overall complication rates were also higher after MTOP, although this only achieved statistical significance in the preference arm. Overall, STOP cost more than MTOP due to higher inpatient standard costs. Even though complication rates were higher with MTOP, it was still more cost-effective. DCE identified three attributes with an almost equal impact on women’s preferences: provision of counselling, number of days delay to the procedure, and possibility of an overnight stay. Conclusions: MTOP was associated with more negative experiences of care and lower acceptability. Acceptability of MTOP declined with increasing gestational age. MTOP was less costly but also less effective than STOP. The majority of women choosing MTOP were satisfied with their care and found the procedure acceptable. Recommendations for further research: An audit of provision of MTOP and STOP in England and Wales is urgently required. Further studies exploring the barriers to offering women the choice of method of TOP are needed, together with research on the acceptability and effectiveness of (1) MTOP and manual VA in pregnancies below 9 weeks’ gestation and (2) MTOP and dilatation and evacuation after 14 weeks’ gestation. Trial registration: Current Controlled Trials ISRCTN07823656.